Plasmodium falciparum var genes expressed in children with severe malaria encode CIDRα1 domains - Jakob S Jespersen; Christian W Wang; Sixbert I Mkumbaye; Daniel TR Minja; Bent Petersen; Louise Turner; Jens EV Petersen; John PA Lusingu; Thor G Theander; Thomas Lavstsen (EMBO Molecular Medicine, 2016)
Abstract Most severe Plasmodium falciparum infections are experienced by young children. Severe symptoms are precipitated by vascular sequestration of parasites expressing a particular subset of the polymorphic P. falciparum erythrocyte membrane protein 1 (PfEMP1) adhesion molecules. Parasites binding human endothelial protein C receptor (EPCR) through the CIDRα1 domain of certain PfEMP1 were recently associated with severe malaria in children. However, it has remained unclear to which extend the EPCR‐binding CIDRα1 domains epitomize PfEMP1 expressed in severe malaria. Here, we characterized the near full‐length transcripts dominating the var transcriptome in children with severe malaria and found that the only common feature of the encoded PfEMP1 was CIDRα1 domains. Such genes were highly and dominantly expressed in both children with severe malarial anaemia and cerebral malaria. These observations support the hypothesis that the CIDRα1‐EPCR interaction is key to the pathogenesis of severe malaria and strengthen the rationale for pursuing a vaccine or adjunctive treatment aiming at inhibiting or reducing the damaging effects of this interaction.